Light Intensity-dependent Variation in Defect Contributions to Charge Transport and Recombination in a Planar MAPbI3 Perovskite Solar Cell - Ryu, Shinyoung; Nguyen, Duc Cuong; Ha, Na Young; Park, Hui Joon; Ahn, Y. H.; Park, Ji Yong; Lee, Soonil (Scientific Reports, 2019)
We investigated operation of a planar MAPbI3 solar cell with respect to intensity variation ranging from 0.01 to 1 sun. Measured J-V curves consisted of space-charge-limited currents (SCLC) in a drift-dominant range and diode-like currents in a diffusion-dominant range. The variation of power-law exponent of SCLC showed that charge trapping by defects diminished as intensity increased, and that drift currents became eventually almost ohmic. Diode-like currents were analysed using a modified Shockley-equation model, the validity of which was confirmed by comparing measured and estimated open-circuit voltages. Intensity dependence of ideality factor led us to the conclusion that there were two other types of defects that contributed mostly as recombination centers. At low intensities, monomolecular recombination occurred due to one of these defects in addition to bimolecular recombination to result in the ideality factor of ~1.7. However, at high intensities, another type of defect not only took over monomolecular recombination, but also dominated bimolecular recombination to result in the ideality factor of ~2.0. These ideality-factor values were consistent with those representing the intensity dependence of loss-current ratio estimated by using a constant internal-quantum-efficiency approximation. The presence of multiple types of defects was corroborated by findings from equivalent-circuit analysis of impedance spectra.